Black Scholarly Activism between the Academy and Grassroots A Bridge for Identities and Social Justice - Clennon, Ornette D. (Springer International Publishing, 2018)
'This is a timely and important book that expertly combines personal narrative with nuanced theoretical analysis. Black Scholarly Activism between the Academy and Grassroots is a deeply engaging work that urges the reader to consider the possibilities and challenges facing academics who work towards social justice. Once picked up, this is a difficult book to put down: a must read.' -Remi-Joseph Salisbury, Leeds Beckett University, UK This book explores the 'invisible' impact whiteness has on the lived 'black' experience in the UK. Using education as a philosophical and ethical framework, the author interrogates the vision of Black Radicalism proposed by Kehinde Andrews, exploring its potential applicability to grassroots activism. Clennon uses an interdisciplinary theoretical framework to draw together his previous writings on 'blackness', in effect crystallising the links between commercial (urban) blackness, the pathological structures of whiteness and institutional control. Drawing inspiration from Robbie Shilliam's cosmologically related 'hinterlands' as an antidote to the nature of colonial (Eurocentric) epistemologies, the author uses the polemical chapters as gateways to theoretical discussion about the material effects of whiteness felt on the ground. This controversial and unflinching volume will be of interest to students and scholars of race studies, particularly within education, and the lived black experience. Ornette D. Clennon is a Visiting Research Fellow at Manchester Metropolitan University, UK. He is also an activist and writer, working both at local and national levels, and in 2011 received the NCCPE Beacons New Partnerships Award for his enterprise and activism work.